AcetoBase Version 2: a database update and re-analysis of formyltetrahydrofolate synthetase amplicon sequencing data from anaerobic digesters. (16th June 2022) - Singh, Abhijeet; Schnürer, Anna
Abstract: AcetoBase is a public repository and database of formyltetrahydrofolate synthetase (FTHFS) sequences. It is the first systematic collection of bacterial FTHFS nucleotide and protein sequences from genomes and metagenome-assembled genomes and of sequences generated by clone library sequencing. At its publication in 2019, AcetoBase (Version 1) was also the first database to establish connections between the FTHFS gene, the Wood–Ljungdahl pathway and 16S ribosomal RNA genes. Since the publication of AcetoBase, there have been significant improvements in the taxonomy of many bacterial lineages and accessibility/availability of public genomics and metagenomics data. The update to the AcetoBase reference database described here (Version 2) provides new sequence data and taxonomy, along with improvements in web functionality and user interface. The evaluation of this latest update by re-analysis of publicly accessible FTHFS amplicon sequencing data previously analysed with AcetoBase Version 1 revealed significant improvements in the taxonomic assignment of FTHFS sequences. Database URL : https://acetobase.molbio.slu.se